2002
DOI: 10.1038/419802a
|View full text |Cite
|
Sign up to set email alerts
|

One nostril knows what the other learns

Abstract: Before exposure, the experimental group (Fig. 1a) showed 25% accuracy (s.d. 11%), which is not significantly different from 33% chance (binomial from chance: Pǃ0.9). Exposure for 21 days doubled the androstenone-detection accuracy in both the exposed nostril (from 25% to 55%, change from baseline: t(11)ǃ3.3, P<0.007; binomial from chance: P<0.002) and the unexposed nostril (from 25% to 49%, change from baseline: t(11)ǃ2.3, P<0.04; binomial from chance: P<0.02). There was no significant difference in the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 11 publications
4
73
0
1
Order By: Relevance
“…In addition, none of our subjects reported sexual arousal. Another tentative explanation is that the observed activation with AND in HeW reflected an acquired sensitization to its stimuli in the hypothalamus or its centrifugal networks due to the repeated exposure to men through life sexual experience (38). However, sensitization can be acquired to several odorants and more easily in women (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, none of our subjects reported sexual arousal. Another tentative explanation is that the observed activation with AND in HeW reflected an acquired sensitization to its stimuli in the hypothalamus or its centrifugal networks due to the repeated exposure to men through life sexual experience (38). However, sensitization can be acquired to several odorants and more easily in women (39).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could reflect an acquired sensitization to AND stimuli in the hypothalamus or its centrifugal networks, due to repeated sexual exposure to men (35). A third possibility is that HeW and HoM associated AND with sex, whereas HeM made a similar association with EST.…”
Section: Discussionmentioning
confidence: 99%
“…First, Yee and Wysocki (2001) found that olfactory nerve transaction in mice before repetitive androstenone exposure did not prevent the process of exposure-induced sensitization, strongly implicating the olfactory epithelium in the changes. Secondly, Mainland et al (2002), by repetitively exposing only one nostril to androstenone and demonstrating enhanced sensitivity when stimulating the contralateral nostril, proposed that the induced detection originated in central components of the olfactory system, although they did not rule out a contribution from the plasticity of peripheral components (ie the olfactory epithelium). The third study, by Wang et al (2004a), demonstrated that the electro-olfactogram (EOG) in response to androstenone stimulation, increased following repetitive exposure to androstenone, supporting the notion of peripheral olfactory plasticity.…”
Section: Introductionmentioning
confidence: 99%